Restoration of Impact Damage in Polymers via a Hybrid Microcapsule–Microvascular Self‐Healing System. (23rd November 2017) - Gergely, Ryan C. R.; Santa Cruz, Windy A.; Krull, Brett P.; Pruitt, Emmy L.; Wang, Jonathan; Sottos, Nancy R.; White, Scott R.
Abstract: A hybrid microcapsule–microvascular system is introduced to regenerate the multiscale damage that results from impact puncture of vascularized polymeric sheets. Microvascular delivery of a two‐stage healing agent restores lost damage volume (puncture) to recover impact energy absorption, while embedded microcapsules heal microcracks to facilitate sealing. Modulation of the mechanical properties (1.4 GPa to 1.1 MPa stiffness) of the healing agent after curing is achieved by selection of compatible reactive acrylate monomers. Specimens are punctured and the impacted hole and surrounding damaged volume is restored by delivering the two‐stage healing agents to the site of damage via a microvascular network. Rapid gelling of two‐stage healing agents enables their retention in the damage region, while subsequent polymerization recovers structural performance. Impact recovery efficiency is assessed in terms of energy absorption, comparing reimpacted specimens to the initial impact. Recovery of impact energy absorption as high as 100% is observed for the optimal specimen design. Specimens are tested for sealing under static pressurization to monitoring leakage through the restored damage. A hybrid system incorporating both microvascular delivery of the two‐stage healing agents and microcapsules containing solvated epoxy enables sealing of 100% of specimens. Abstract : A hybrid system incorporates both microcapsules and microvascular delivery for the restoration of impact puncture damage . Multiscale damage is addressed by multiple healing modes: two‐stage healing agents delivered through a dual microvascular network restore lost material volume in order to recover impact energy absorption, while embedded microcapsules heal radiating microcracks to facilitate sealing and recovery of barrier properties.